Discussão de critérios de operação de sistemas hidrelétricos interligados - Cunha, Laertes Munhoz da (1986)
The increasing complexity of the Brazilian hydro-thermal electrical generation system demands the adoption of several simplifying assumptions to allow its modelling and thus permit the solution to the problem of determining its optimal operation. However, this simplified representation of the system has implicit erros which may give the wrong idea on the gains from a more efficient operation of the thermal plants. Such possibility justify a deeper analysis of the problem, considering only the hydroelectric power plants which, in Brazil, represent the largest source of power generation. This thesis explores simplified stochastic models in order to obtain optimum operation rules for interconnected hydropower systems according to two different criteria. It also presents the consequences of adopting each criterion specially in regard to the flows of energy among systems. Generally in such studies, mathematical programming techniques are used, mainly Dynamic Programming. However, in this work, a closed form solution was searched, corresponding to the Stochastic Dynamic Programming solution, with the simplification of only one stage being considered in the planning horizon. The objective functions analysed are a consequence of interconnected operation, where advantadges are taken from hydrological diversity among regions. The first criterion minimizes the expected sum of the energy overflows in each system and the second criterion minimizes the expected sum of the energy deficits in each system. ln each case, only one stage of the planning horizon is considered.